Chitooligosaccharide-induced plant stress resistance. (15th February 2023) - Liu, Yao; Yang, Hehe; Wen, Fang; Bao, Liangliang; Zhao, Zhihong; Zhong, Zhimei
Abstract: In nature, the production of plant stress resistance traits is often induced by extreme environmental conditions. Under extreme conditions, plants can be irreversibly damaged. Intervention with phytostimulants, however, can improve plant stress resistance without causing damage to the plants themselves, hence maintaining the production. For example, exogenous substances such as proteins and polysaccharides can be used effectively as phytostimulants. Chitooligosaccharide, a plant stimulant, can promote seed germination and plant growth and development, and improve plant photosynthesis. In this review, we summarize progress in the research of chitooligosaccharide-induced plant stress resistance. The mechanism and related experiments of chitooligosaccharide-induced resistance to pathogen, drought, low-temperature, saline-alkali, and other stresses are classified and discussed. In addition, we put forward the challenges confronted by chitooligosaccharide-induced plant stress resistance and the future research concept that requires multidisciplinary cooperation, which could provide data for the in-depth study of the effect of chitooligosaccharide on plants. Graphical abstract: Unlabelled Image